Teori Belajar dan Pembelajaran - Abdurakhman, Omon; Rusli, Radif Khotamir (Universitas Djuanda, 2015)
Learning theory is the core matter for a teacher in learning practices for students. This is related to the teacher's professional ability in carrying out its main task in teaching. If associated with a national education program, that a teacher must have sufficient scientific in pedagogical science, the theory of learning is a fundamental. Therefore, this paper will discuss some theories about teaching and learning in which is worldwidely known among education experts. The methodology used in this work is a model of descriptive qualitative analysis which is outlining a theory in detail so as to enable the reader to gives more inâ€depth analysis. Therefore, the content of theories might slightly simple, but the explanation will be essential matter.